Reconceptualizing Public Innovation Sustainability: A Non-Western Administrative Perspective - Lugas Ari Nur Ridwan Ridwan; Drajat Tri Kartono; Rina Herlina Haryanti (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2026)
Abstract Public innovation sustainability remains a critical challenge in contemporary governance reform, as many initiatives fail to endure beyond their initial implementation phase. Mainstream public administration literature predominantly explains sustainability through managerial and formal institutional approaches rooted in Western paradigms, emphasizing regulation, leadership stability, organizational capacity, and accountability mechanisms. However, such perspectives are insufficient to explain variation in innovation endurance across governance systems characterized by institutional hybridity, contextual legitimacy dynamics, and complex state–society relations. This study aims to develop a conceptual framework for public innovation sustainability through the lens of Non-Western Public Administration (NWPA). Using a qualitative conceptual design grounded in systematic literature exploration and interpretative synthesis of scholarship published between 2000 and 2025, supplemented by foundational institutional theory, this study reconceptualizes sustainability as a socio-institutional and configurational process. The findings demonstrate that innovation endurance emerges from the dynamic alignment among contextual institutionalization, adaptive managerial capacity, sustainable resource support, and collaborative governance, mediated by social legitimacy and embeddedness. Sustainability, therefore, is not merely administrative stabilization but an ongoing process of institutional reproduction within a governance ecology. By integrating relational and contextual mediating mechanisms into institutional approaches, this study extends public innovation theory and offers a more context-sensitive analytical model for explaining sustainability variation across diverse governance systems. Keywords: public innovation; innovation sustainability; non-Western public administration; contextual governance; social legitimacy.   Abstrak   Keberlanjutan inovasi publik tetap menjadi tantangan kritis dalam reformasi tata kelola kontemporer, karena banyak inisiatif gagal bertahan melampaui fase implementasi awalnya. Literatur mainstream administrasi publik secara dominan menjelaskan keberlanjutan melalui pendekatan manajerial dan institusional formal yang berakar pada paradigma Barat, dengan menekankan pada regulasi, stabilitas kepemimpinan, kapasitas organisasi, dan mekanisme akuntabilitas. Namun, perspektif tersebut tidak memadai untuk menjelaskan variasi daya tahan inovasi di berbagai sistem tata kelola yang dicirikan oleh hibriditas institusional, dinamika legitimasi kontekstual, dan hubungan negara-masyarakat yang kompleks. Berdasarkan eksplorasi literatur secara sistematis dan sintesis interpretatif terhadap karya ilmiah dari tahun 2000 hingga 2025, yang dilengkapi dengan teori institusional dasar, studi ini menggunakan desain konseptual kualitatif untuk merekonseptualisasi keberlanjutan sebagai proses sosio-institusional dan konfigurasional. Temuan penelitian menunjukkan bahwa daya tahan inovasi muncul dari penyelarasan dinamis antara institusionalisasi kontekstual, kapasitas manajerial yang adaptif, dukungan sumber daya yang berkelanjutan, dan tata kelola kolaboratif, yang dimediasi oleh legitimasi sosial dan keterikatan (embeddedness). Oleh karena itu, keberlanjutan bukan sekadar stabilisasi administratif, melainkan sebuah proses reproduksi institusional yang berkelanjutan dalam suatu ekologi tata kelola. Dengan mengintegrasikan mekanisme mediasi relasional dan kontekstual ke dalam pendekatan institusional, studi ini memperluas teori inovasi publik dan menawarkan model analisis yang lebih sensitif terhadap konteks untuk menjelaskan variasi keberlanjutan di berbagai sistem tata kelola yang beragam.   Kata kunci: inovasi publik; keberlanjutan inovasi; administrasi publik non-Barat; tata kelola kontekstual; legitimasi sosial.